The Ominous Eye : The Nocturnals Series #2 - Hecht, Tracey; Liebman, Kate (New York : Fabled Films Press, 2016)
The Nocturnal brigade, Dawn the fox, Tobin the pangolin, and Bismark the sugar glider investigate the source of a violent jolt that fractures the earth and meet a tuatara named Polyphema who has information on the event.
Keywords: Nocturnal animals -- Fiction; Adventure and adventurers -- Fiction; Mystery and detective stories; Nocturnal animals -- Fiction; Humorous fiction; Adventure fiction; Mystery fiction; Humorous fiction